Hierarchical NiCo2O4 needle-like heterostructure arrays anchored on WO3 as high- performance asymmetric supercapacitors for energy storage applications - Siveswari A; Gowthami V (Chemical Physics Impact)
The current work employs a novel approach to construct a composite nanostructure to improve the capacitive performance of a supercapacitor device. The work involved preparing cube-shaped WO3 particles and depositing them onto the surface of NiCo2O4 needles using a microwave technique. The structure of the composites enables efficient paths for ion transport and electron diffusion in supercapacitors. The hybrid composite electrode demonstrates a specific capacitance of 716 F g−1 at a current density of 5 Ag−1. The asymmetric capacitor device, which utilizes NiCo2O4@WO3 as the positive electrode and AC as the negative electrode, exhibits an energy density of 48.57 Wh kg−1 at a power density of 1120 W kg−1. In addition, the NiCo2O4@WO3//AC device has a favourable cycle life, maintaining 85.7 % of its capacitance retention after 10,000 cycles. The findings demonstrate the potential of NiCo2O4@WO3//AC to be used in the development of advanced hybrid electrodes for improved supercapacitors.